Ketogenic diet as a successful early treatment modality for SCN2A mutation - TÜRKDOĞAN, DİLŞAD (ELSEVIER SCIENCE BV, 2019)
SCN2A mutations have been described in a very broad spectrum of clinical phenotypes including benign (familial) neonatal/ infantile seizures and early infantile epileptic encephalopathies (EIEE) as Ohtahara syndrome (OS), Dravet syndrome (DS), epilepsy of infancy with migrating focal seizures and West syndrome (WS). Treatment modalities for epilepsy caused by SCN2A mutations mainly consist of sodium channel blockers but ketogenic diet (KD) is also considered as an option of treatment for intractible seizures caused by SCN2A mutations. Because of the wide nature of the heterogeneity of mutations related to SCN2A gene, the clinical phenotypes vary in severity and treatment response to KD has been reported to be controversial. We present a patient diagnosed with OS associated with a novel SCN2A mutation (c.408G > A, p.Met136lle; OMIM (R): 182390) who had a complete resolution of seizures and EEG abnormalities with KD commenced at 39 days of age. As far as we are aware our case is the youngest patient with SCN2A mutation treated with KD with complete resolution of epilepsy at an early age and has been seizure free of antiepileptic medications for a long duration. (C) 2018 The Japanese Society of Child Neurology. Published by Elsevier B.V. All rights reserved.
Keywords: SCN2A mutation; Intractible seizures; Ketogenic diet; EPILEPSY